INNOVATIVE APPROACHES IN DISTANCE LEARNING FOREIGN LANGUAGES - Крекотень, Елена (SWorldJournal, 2021)
This article is aimed at the research of innovative approaches in foreign language distance teaching. Problems of Ukrainian higher education institutions during the period of distance learning have been revealed. The analysis of scientific literature has